Fertility awareness in 97,414 women trying to conceive: gaps, misconceptions, and implications for reproductive education - Esther Wainwright; Zoya Ali; Lucinda Lawrie; Natalie Getreu; Helen C. O’Neill (Reproductive Health)
Abstract Background Fertility rates in the UK are at an all-time low, with infertility affecting approximately 1 in 7 couples. Despite the rising demand for fertility services, fertility awareness, specifically knowledge of ovulation and the fertile window, remains low among women of reproductive age. Most existing studies offer a broad perspective, lacking focus on women actively trying to conceive (TTC). This study aims to assess the level of understanding surrounding the fertile window among women TTC, identifying factors associated with knowledge gaps. Methods A retrospective, cross-sectional analysis of 97,414 women actively TTC who answered an online health assessment was conducted. Participants provided information on menstrual cycle characteristics, previous pregnancies, and fertility knowledge, including the timing of the fertile window. Frequencies, percentages were calculated and chi-squared tests performed to assess differences in categorical data. Logistic regression models were used to calculate odds ratios (ORs) to better understand factors significantly associated with not knowing the fertile window. Results Out of the total respondents (97,414), over a third (33,756, 41%) could not accurately identify the fertile window, with substantial misconceptions observed across all age groups and ethnicities. Women with previous pregnancies were more likely to correctly identify the fertile window (OR = 1.45, 97.5% CI: 1.20–1.75, p < 0.001). However, knowledge was significantly lower among those with irregular cycles, non-White ethnicities, younger age groups and longer time TTC. Additionally, misconceptions about cycle regularity were apparent, of 60,322 women describing their cycles as regular 10% did not know their cycle length (66,95) and a further 2.9% fell outside of the clinically regular 21–35 day range. These misconceptions followed a similar trend with younger age groups, non-white ethnicities and longer time TTC having significantly increased rates of misidentifying regular cycles. This further increased the odds of not knowing their fertile window (OR = 2.99, 97.5% CI: 2.83–3.17, p < 0.001). Conclusions The findings reveal gaps in fertility awareness among women actively TTC. Addressing these knowledge gaps through targeted educational interventions could potentially reduce time-to-pregnancy and the reliance on assisted reproductive technologies. Improved fertility education focusing on cycle tracking and ovulation timing is essential to assist women with accurate information during their TTC journey.